Do dial para a web: as RadCom legalizadas nos fluxos dos espaços em rede - Ferreira, Gisele Sayeg Nunes (2012)
The object of this research is the RadCom (community radio) on the web and its main goal is to understand how these legally constituted to operate stations on the dial organize themselves and build distinct spatialities in his transposition into the web environment. The research also proposes to contribute to the reflections that involve the ways in which the space is organized in media systems, leading to the construction of senses; this way it relates to other studies that have the spatialities as categories of analysis. Based on this main issue, other problems are investigated, such as: the new contours that supported notions of RadCom acquire in the space of flows, including citizenship, participation and community; and how, in new ambience, other storage practices, transmission and reception come to incorporate the communication pattern based on the dial, introducing new practices and generating new terms, how to annotate, comment, aggregate, share, download, upload, and crowdsourcing (Manovich, 2008). Built to be seen (and also manipulated, distributed, shared, etc.), being heard, RadCom on the web in configure "something else". Hence, in the transposition into the space of flows, in addition to the transmutation of the concept of community to the networks (COSTA, R., 2005a), we can also see on the displacement of communicative broadcasting to the interactive linking (FERRARA, 2008, 2012). So, signals-if the offset of the feeling of neighborhood for a sense of topical belonging in ur-topical spatiality, because, in addition to multiple, new places built carry new senses that refer both to the idea of origin/home as principle/permanence. As analysis corpus of the research, were selected the most representative experiences between the legalized RadCom 304 to operate on the dial in the State of São Paulo, located also on the web, until 16 may 2012. In addition to the documentary and bibliographic research and survey of RadCom legalized present also in the web, the method of analysis included the observation and analysis of web pages through the application of a questionnaire previously elaborated, as well as the data tab and comparative reading of modes of organization of space, according to the categories of spatiality, which are: own spatiality (the space-constructibility), visuality/visibility and communicability. As a methodology, the authors who will serve as the theoretical basis are FERRARA (2002, 2007, 2008, 2012), CASTELLS (1999, 2009), MCLUHAN (2007), MCLUHAN and STAINES (2005), LOTMAN (1996), MANOVICH (2005, 2008), BALSEBRE (2007), JOHNSON (2001, 2003), FLUSSER (2007) and THOMPSON (1998)